Blick auf den Hafen von Nain mit Booten wegziehender Eskimos : [ca. 1927] (2001)
Black and white photograph of boats leaving the harbour at Nain, circa 1927. Black and white photograph of boats leaving the harbour at Nain, circa 1927.